Nanofiltration 2018
DOI: 10.5772/intechopen.75819
|View full text |Cite
|
Sign up to set email alerts
|

Electrically and Electrochemically Assisted Nanofiltration: A Promising Approach for Fouling Mitigation

Abstract: Membrane fouling is regarded as the most critical bottleneck for the widespread application of membrane separation technology. The application of electricity to the surface of membrane provides a promising alternative for fouling mitigation, which may involve the following effects such as electrophoresis, electroosmosis, and electrooxidation. Electrophoresis and electroosmosis influence the movement of charged species (ions or molecules) or movement of fluid adjacent to charged surface under the applied electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…Electroosmosis offers another effective method for membrane fouling mitigation by removing bound water from sludge flocs through the application of an electric field. This process induces migration of water molecules towards the cathode, reducing interaction forces between water molecules and sludge particles, resulting in drier sludge and reduced fouling (Ping & Guohua, 2018). Research on an AnOMEBR demonstrated a 26% reduction in the concentration of soluble microbial products and enhanced electrostatic repulsion between the charged membrane surface and foulants, leading to significantly lower cake layer thickness compared to conventional AnMBRs (Xu et al, 2020).…”
Section: Figure 3 Schematic Representation Of Membrane Fouling Allevi...mentioning
confidence: 99%
“…Electroosmosis offers another effective method for membrane fouling mitigation by removing bound water from sludge flocs through the application of an electric field. This process induces migration of water molecules towards the cathode, reducing interaction forces between water molecules and sludge particles, resulting in drier sludge and reduced fouling (Ping & Guohua, 2018). Research on an AnOMEBR demonstrated a 26% reduction in the concentration of soluble microbial products and enhanced electrostatic repulsion between the charged membrane surface and foulants, leading to significantly lower cake layer thickness compared to conventional AnMBRs (Xu et al, 2020).…”
Section: Figure 3 Schematic Representation Of Membrane Fouling Allevi...mentioning
confidence: 99%